Zgodovina slovanske mitologije v XX. stoletju - Mihajlov, Nikolaj (ZRC SAZU, Založba ZRC, 2022)
This book by the renowned Russian linguist and semiotician Nikolai Mikhailov [Николай Александрович Михайлов] (1967–2010) is now published posthumously, more than ten years after his death. Presented is analytic overview of numerous past studies on Slavic and Balto-Slavic mythology. Included are works written by scholars of Slavic mythology based on written sources as well as on findings from folklore, linguistics, and archaeology. The first analysed is the work of the Lusatian-Serbian author Michael Frenzl on Slavic idols, which was written as early as 1691 but not published until 1719. It is followed by treatises and monographs that span across three centuries. The so-called original sources (reports of chroniclers, archaeological sources) may be incomplete and obscure, yet they are in this book again critically analysed. The author reconstructed the mythology of various Slavic nations partly also through the remnants of paganism that have survived to this day in various and often highly modified forms.